Performance of Composite Paste Barricades at Goldcorp Inc., Red Lake Mine, Ontario, Canada - Hughes, PB; Pakalnis, R; Hitch, M; Corey, G (Paste 2009: Proceedings of the Twelfth International Seminar on Paste and Thickened Tailings, 2009)
Appropriate strength barricades and fill fences are a necessary component of underhand cut and fill mining operations and stoping operation in general. These important structures are subject to a number of stresses and strains as a result of the deposition, and curing of the backfill material. Parametric monitoring of fill fences gives the engineer the required data to predict not only the behaviour of the paste backfill as it is being deposited but also the ability to predict the deformation and eventual failure of the barricade. A study was undertaken to determine the performance of the paste barricades at Goldcorp Inc.’s Red Lake Mine using real time instrumentation to monitor the stresses, strains and deformation of paste and paste barricades during placement. The barricades at the mine are a standardised barricade comprised of 10 cm of shotcrete applied to a rebar skeleton spaced nominally 60 cm apart. In total eight fill barricades were instrumented to determine the behaviour of the paste during the loading. Complementing the eight barricade tests, an instrumented destructive test was carried out to determine the ultimate capacity of the composite barricade. It was determined that the paste backfill behaves as a Rankine-like soil in the initial stages of placement with an average coefficient of lateral earth pressure, Ka, of 0.56. The destructive test determined that the yielding stress of a paste barricade is approximately 100 kPa. The results of the investigation have resulted in operational changes in the placement of paste at the mine.